Economic sustainability in safari tourism in Southeast Asia: the case of Minneriya National Park Sri Lanka / Madura Thivanka Pathirana ... [et al.] - Pathirana, Madura Thivanka; Herath, H.M.R.P.; Scott, Noel; Gardiner, Sarah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Safari Tourism in Sri Lanka is a key selling factor for Sri Lanka tourism. However, less attention has been paid to the economic sustainability of the service and driving them to the long-term survival, particularly the extent which the safari tourism is creating value and delivering value to the customer sustainably. Therefore, aim of this paper is to consider about the existing status of the safari tourism operators in Sri Lanka and redeveloping the business model to drive and promote the economic sustainability. This paper is a case study for Minneriya National park. One safari operator has selected based on the level of experience to collect the evidence. Interview guides were prepared using the key model of this paper that is business model canvas. Later, coding was applied to derive the emerging themes and patterns to redevelop the business model. Drawing the research in Minneriya National Park and with the case study operator it reveals the way in how to operate the safari tourism to an economic sustainability. Proposed business model was further explained with the implementation advice with the willingness to implementation of those elements.